El bilingüismo en la formación de educadores infantiles - Mosquera Muñoz, Claudia Judith (Reflexiones metodológicas y epistemológicas en torno a las prácticas pedagógicas contemporaneas, 2021)
The chapter involves different reflections on bilingualism in our region which contributes to the development the National Bilingualism Program, which includes the new standards of communicative competence in a foreign language. The University of Pamplona and the Foreign Language Degree concern about this issue are providing the tools, researching and projects to contribute to the community in the acquisition of a second language with the help of our bilingual student-teachers, who work hard to develop different methodologies and strategies to teach English as a second language